Larval Mid-Gut Responses to Sub-Lethal Dose of Cry Toxin in Lepidopteran Pest Achaea janata - Chauhan, Vinod K.; Dhania, Narender K.; Chaitanya, R. K.; Senthilkumaran, Balasubramanian; Dutta-Gupta, Aparna (Frontiers in Physiology, 2017)
The lack of homogeneity in field application of Bacillus thuringiensis formulation often results in ingestion of sub-lethal doses of the biopesticide by a fraction of pest population and there by promotes the toxin tolerance and resistance in long term. Gut regeneration seems to be one of the possible mechanism by which this is accomplished. However, the existing information is primarily derived from in vitro studies using mid-gut cell cultures. Present study illustrates cellular and molecular changes in mid-gut epithelium of a Bt-susceptible polyphagous insect pest castor semilooper, Achaea janata in response to a Cry toxin formulation. The present report showed that prolonged exposure to sub-lethal doses of Cry toxin formulation has deleterious effect on larval growth and development. Histological analysis of mid-gut tissue exhibits epithelial cell degeneration, which is due to necrotic form of cell death followed by regeneration through enhanced proliferation of mid-gut stem cells. Cell death is demonstrated by confocal microscopy, flow-cytometry and DNA fragmentation analysis. Cell proliferation in control versus toxin-exposed larvae is evaluated by bromodeoxyuridine (BrdU) labelling and toluidine blue staining. Intriguingly, in situ mRNA analysis detected the presence of arylphorin transcripts in larval mid-gut epithelial cells. Quantitative PCR analysis further demonstrates altered expression of arylphorin gene in toxin-exposed larvae when compared with the control. The coincidence of enhanced mid-gut cell proliferation coincides with the elevated arylphorin expression upon Cry intoxication suggests that it might play a role in the regeneration of mid-gut epithelial cells.